New host, geographical records, and some ecological aspect of Absonifibula bychowskyi lawler et overstreet, 1976 (Monogenea: Diclidophoridae) from estuarine areas of Argentina - Martorelli, Sergio Roberto (2007)
Background. Monogenean parasites from mixohaline areas of the South Atlantic coast of Argentina are very poorly reported. The aim of this paper is report a new host and locality for Absonifibula bychowskyi, a monogenean confined to fish living in estuarine areas. Some ecological considerations about the host-parasite relationship are also discussed. Materials and Methods. Parasites collected from whitemouth croaker, Micropogonias furnieri (Desmarest, 1823) (Actinopterygii: Sciaenidae), were studied from fixed- and live specimens, with standard procedures used in parasitology. Prevalence, mean intensity, and abundance of parasites were calculated and related to the host body size. Spearman's rank correlation coefficient was calculated to determine possible correlations between host length, parasite intensity, and prevalence. Results. Absonifibula bychowskyi (Monogenea: Diclidophoridae) Lawler et Overstreet, 1976 is reported for the first time from the gills of whitemouth croaker, at the Samborombón Bay, a mixohaline area in the Buenos Aires Province, Southwest Atlantic Ocean. The parasite was found only in juveniles of M. furnieri that use the Samborombón Bay as the main estuarine nursery ground area. When the croaker migrated seawards, A. bychowskyi disappeared from the gills may be related to the increased salinity. Conclusions. This is the first record for Absonifibula bychowskyi in the Southwest Atlantic and M. furnieri. (It constitutes a new host record.) The presence of A. bychowskyi in M. furnieri could be indicative of the origin of the fish.